The Nutrition Care Process in Hospitalized Patients with Chronic Kidney Disease Stage V, Pancytopenia, and Hypertension - Herviana; Kiki Rizky Ananda; Eka Rusliana; Wiwik Ekorinawati; Helmi Susanti Simamora (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Patients with chronic kidney disease undergoing hemodialysis require proper nutritional management to prevent malnutrition. This is because the hemodialysis process can cause protein loss and energy imbalance. Objectives the aim of this research is analyzing the Standardized Nutrition Care Process carried out in hospitalized patients with CKD at Moewardi Hospital Surakarta. This study is a descriptive study with case studies. Data were collected through patient interviews and analysis of medical records. Monitoring and evaluation of nutritional care were conducted over a period of 3 days. Indicators used for monitoring included anthropometric data, biochemistry, physical clinical data, and food intake through a 24-hour recall form. Results, a low-sodium dialysis diet (LS) III was prescribed to the patient, with the Schofield formula being used to determine nutrition requirements. The required energy was 2102.64 kcal, with 69.44 g of protein, 70.08 g of fat, and 298.54 g of carbohydrates. The daily limit of sodium was set at 1-2 mEq/KgBW because of hypertension and edema. Soft food was provided three times a day for main meals and two times a day for snacks. After three day monitoring period, there was an increase in patient intake however, it remained below the target level of 70%. In this case, the patient's intake increased on day 2, but on day 3 there was a decrease in intake due to the patient's unstable condition. As a result, the interventions carried out had to be adjusted to align with the patient's condition.